The Digital Transformation Leadership Framework: Conceptual and Empirical Insights into Leadership Roles in Technology-Driven Business Environments - Ellen Weber; Eva-Helen Krehl; Marion Büttgen (Journal of Leadership Studies, 2022)
The powerful and disruptive changes associated with digital transformation make leadership more complex than before, which results in new and demanding challenges for companies and leaders alike. Thus, building on the competing values framework (CVF), which postulates that leaders must adopt multiple roles and behaviors, the current research aims to identify leadership roles appropriate in digital transformation and subsequently investigate whether the existing CVF roles are still relevant. A qualitative study was conducted to identify appropriate leadership behaviors in digital transformation. Additionally, a measurement scale for the identified leadership roles was developed and tested. Furthermore, multidimensional scaling (MDS) was used to test the degree-of-fit between the identified leadership roles in digital transformation and the four CVF quadrants. The results reveal that new leadership roles emerge in the context of digital transformation. Some original CVF roles are still relevant, but others should be modified. Overall, the findings indicate that leaders need a broad behavioral complexity to master the emerging leadership challenges in digital transformation.
Keywords: 650